Patient‐based radiographic exposure factor selection: a systematic review. Issue 3 (7th August 2014) - Ching, William; Robinson, John; McEntee, Mark
Abstract Introduction Digital technology has wider exposure latitude and post‐processing algorithms which can mask the evidence of underexposure and overexposure. Underexposure produces noisy, grainy images which can impede diagnosis and overexposure results in a greater radiation dose to the patient. These exposure errors can result from inaccurate adjustment of exposure factors in response to changes in patient thickness. This study aims to identify all published radiographic exposure adaptation systems which have been, or are being, used in general radiography and discuss their applicability to digital systems. Methods Studies in EMBASE, MEDLINE, CINAHL and SCOPUS were systematically reviewed. Some of the search terms used were exposure adaptation, exposure selection, exposure technique, 25% rule, 15% rule, DuPont™ Bit System and radiography. A manual journal‐specific search was also conducted in The Radiographer and Radiologic Technology. Studies were included if they demonstrated a system of altering exposure factors to compensate for variations in patients for general radiography. Studies were excluded if they focused on finding optimal exposures for an 'average' patient or focused on the relationship between exposure factors and dose. Results The database search uncovered 11 articles and the journal‐specific search uncovered 13 articles discussing systems of exposure adaptation. They can be categorised as simple one‐step guidelines, comprehensive charts and computer programs. Conclusion Only two papers assessed the efficacy of exposure adjustment systems. No literature compares the efficacy of exposure adaptations system for film/screen radiography with digital radiography technology nor is there literature on a digital specific exposure adaptation system.